2022
DOI: 10.3390/pathogens11111391
|View full text |Cite
|
Sign up to set email alerts
|

A New Comestible Formulation of Parasiticide Fungi to Reduce the Risk of Soil-Transmitted Helminth Infections in a Canine Shelter

Abstract: Dogs cared for in a shelter are dewormed every three–four months, but they all become infected one–two months later by the soil-transmitted helminths (STHs) Toxocara canis, Toxascaris leonina, Trichuris vulpis, and Ancylostoma caninum. For the purpose of reducing their risk of infection by decreasing the survival of helminths’ infective stages in soil, chlamydospores of two parasiticide fungi, Mucor circinelloides (ovicide) and Duddingtonia flagrans (larvicide) were formulated as handmade edible gelatins and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Finally, since all Mucor strains were isolated from avian fresh fecal samples, and showed interesting lytic activity on coccidian oocysts, it can be suggested that these strains resisted to the gastrointestinal passage in chickens and peacocks, and maintained both their germination and predatory capacities, as previously demonstrated in birds for the ovicidal fungus P. chlamydosporia 50 and larvicidal fungi D. flagrans and Monacrosporium thaumasium 51 . The fact that all Mucor isolates were obtained from feces belonging to healthy birds, allows also to suggest their innocuity to immunocompetent birds, as demonstrated by other researchers for horses 37 , sheep 20 , dogs 28 and wapitis 19 .…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Finally, since all Mucor strains were isolated from avian fresh fecal samples, and showed interesting lytic activity on coccidian oocysts, it can be suggested that these strains resisted to the gastrointestinal passage in chickens and peacocks, and maintained both their germination and predatory capacities, as previously demonstrated in birds for the ovicidal fungus P. chlamydosporia 50 and larvicidal fungi D. flagrans and Monacrosporium thaumasium 51 . The fact that all Mucor isolates were obtained from feces belonging to healthy birds, allows also to suggest their innocuity to immunocompetent birds, as demonstrated by other researchers for horses 37 , sheep 20 , dogs 28 and wapitis 19 .…”
Section: Discussionmentioning
confidence: 70%
“…Their isolation from fecal matter, which frequently also harbours environmental forms of intestinal parasites, proves that fungi and parasites naturally establish relationships in the fecal and soil microenvironment, with the formers being a nutritional source for predatory fungi 17 , 29 , 36 . Also, the isolation of this type of fungi from feces belonging to healthy animals demonstrates the equilibrium in which these microorganisms are within the intestinal environment, and thus their innocuity to immunocompetent animals 17 , 19 , 20 , 28 , 37 39 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, good faecal hygiene and prompt faecal removal from the environment provides one mechanism to break the life cycle. In addition, use of oral administration of chlamydospores of two parasiticide fungi, Mucor circinelloides (ovicide) and Duddingtonia flagrans (larvicide) demonstrated a significant reduction in hookworm EPG values at the 9th month when comparing two groups of dogs receiving similar anthelmintic treatments in a dog shelter environment ( Viña et al, 2022 ). Maciel et al (2010) specifically looked at the impact of D. flagrans on Ancylostoma spp.…”
Section: Treatment and Control Strategies For Drug Resistant ...mentioning
confidence: 99%
“…R.C. Cooke (1969), Arthrobotrys oligospora Fresen., (1850), and Monacrosporium thaumasium (Drechsler) de Hoog & Oorschot (1985), which are able to destroy nematodes’ infective larvae (L3) (larvicidal fungi), whereas Pochonia chlamydosporia (Goddard) Zare & W. Gams (2001) and Mucor circinelloides Tiegh (1875) present ovicidal activity towards helminth eggs and coccidian oocysts (ovicidal/coccidicidal fungi) 18 , 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%